Enhanced thermoelectric properties of screen-printed Bi0.5Sb1.5Te3 and Bi2Te2.7Se0.3 thick films using a post annealing process with mechanical pressure. Issue 33 (11th August 2017) - Choi, Hyeongdo; Kim, Sun Jin; Kim, Yongjun; We, Ju Hyung; Oh, Min-Wook; Cho, Byung Jin
Abstract : We report on a TE device composed of p-type Bi0.5 Sb1.5 Te3 and n-type Bi2 Te2.7 Se0.3 TE materials prepared using a screen-printing process. Abstract : A cost-effective and large-scale thermoelectric (TE) energy harvester is becoming increasingly important for energy recovery systems such as self-powered electronics and renewable power generation. Here, we report on a TE device composed of p-type Bi0.5 Sb1.5 Te3 and n-type Bi2 Te2.7 Se0.3 TE materials prepared using a screen-printing process, which has the advantages of low cost, scalability to large areas and the ability to form a flexible TE generator. The TE properties of the screen-printed TE thick films were optimized via subsequent annealing with mechanical pressure. It was found that thermal annealing with the application of mechanical pressure plays a key role in controlling the carrier concentration and improving the density of the TE thick films. Under optimized annealing conditions, the Bi0.5 Sb1.5 Te3 (p-type) thick film had a ZT of 0.89 and a density of 5.67 g cm −3 while the Bi2 Te2.7 Se0.3 (n-type) thick film had a ZT of 0.57 and a density of 5.68 g cm −3 at room temperature. TE generators composed of 72 and 200 couples were fabricated with these thick films. The output power of the device composed of 72 couples was 0.1 W for a temperature difference (Δ T ) of 28 K. Another device with 200 couples generated 0.31 W of electric power for the same Δ T .